2017
DOI: 10.3928/19382359-20170725-01
|View full text |Cite
|
Sign up to set email alerts
|

The History of Home Cardiorespiratory Monitoring

Abstract: Home cardiorespiratory monitoring has changed significantly since it was first introduced in the 1970s. It has improved from a simple alarm system to a sophisticated piece of equipment capable of monitoring the patient's electrocardiogram, respiratory effort, and oxygen saturations. In addition, the indications for using a monitor have also changed. The home monitor was initially used to reduce the incidence of sudden infant death syndrome (SIDS). Although there were several studies demonstrating the reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 24 publications
0
21
0
3
Order By: Relevance
“…Use of pulse oximetry and cardiorespiratory monitors in the home setting has been long debated and has been a controversial topic ever since the introduction of such monitors in early 1970s. 6 The history is well summarized in a recent article by Freed and Martinez. 6 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Use of pulse oximetry and cardiorespiratory monitors in the home setting has been long debated and has been a controversial topic ever since the introduction of such monitors in early 1970s. 6 The history is well summarized in a recent article by Freed and Martinez. 6 …”
Section: Discussionmentioning
confidence: 99%
“…Freed and Martinez 6 provided data from a comprehensive home cardiorespiratory monitoring program of more than 35,000 infants from August 1998 to December 2016. Their most recent hypothesis about the utility of cardiorespiratory monitoring suggests that the monitoring of a select group of infants who are at risk for episodes of intermittent hypoxemia has merit and bears serious consideration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this hypothesis was never proven and no prospective data showed an effect on sudden unexpected infant death (SUID) rates, leading to the AAP 94 recommendation against their routine use. 95 The Collaborative Home Infant Monitoring Evaluation Study showed that preterm infants had more events than SIDS siblings, infants that had experienced an apparent life threatening event (ALTE) event or healthy infants. "Extreme events" (apnea >30 seconds and/or heart rate 10 seconds) were common in preterm infants but very rare after 43 weeks postconceptual age.…”
Section: Home Apnea Monitoringmentioning
confidence: 99%
“…They may serve as a diagnostic tool with careful review of downloads suggesting such diagnoses as gastroesophageal reflux, arrhythmias, and seizures, and it has been suggested that an increase in alarms may be an early sign of an respiratory syncytial virus (RSV) infection. 95 Apnea monitors have the potential of being cost-effective devices, enabling early NICU discharge, reducing family costs, and decreasing time off from work. A recent study by Montenegro et al showed that a hypothetical outpatient management plan could lead to $2,422 to $62 being saved per eligible patient.…”
Section: Home Apnea Monitoringmentioning
confidence: 99%